Efektivitas Pendampingan Kepemimpinan Dalam Meningkatkan Kualitas Tata Kelola Pesantren - Febri Irwan Saputra, Mohammad; Nuraini Maulidia, (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Mentoring in leadership is a crucial strategy for enhancing the quality of Islamic boarding school governance, especially amidst the demands of modernization, social dynamics, and the need to strengthen the character of students as future leaders. This Community Service Program (PKM) was implemented to analyze and test the effectiveness of leadership mentoring carried out through training for administrators and room supervisors at Islamic boarding school An-Nur II Putri Bululawang, Malang. The PKM's focus was directed toward how structured mentoring could improve management patterns, strengthen internal coordination, and enhance the quality of the Islamic boarding school educational environment. The implementation methods included participatory observation, in-depth interviews, leadership training, habituation of Islamic leadership values, and weekly coaching for administrators and room supervisors. The mentoring utilized a leadership management approach covering the functions of planning, organizing, directing, and controlling. The results obtained from the activity showed that the mentoring successfully increased the awareness and capacity of the students' leadership, evidenced by improved discipline, successful program execution, the ability to lead small groups, accurate decision-making, and communication skills in problem-solving. Furthermore, the Islamic boarding school governance became more effective through better structural coordination, increased professionalism among administrators, and the formation of a more conducive organizational culture. This mentoring model, which integrates the role modeling of the caretaker, habituation, and technical training, can serve as a reference for other pesantren aiming to strengthen institutional management and build leadership character.